Formulation and testing of locally isolated effective microbes for the development of biofertilizers - Shruti, Prashant Talwar (Universiti Malaysia Sarawak, UNIMAS, 2013)
The soil is a complex and heterogeneous environment constituting a large diversity of effective microbes which can be utilized as biofertilizers. In the present study, local soil samples were collected for isolation of beneficial bacteria. Genomic DNA was extracted from the unknown isolate and subjected to the amplification of 16S rDNA gene for identification. The similarity searching of the sequence obtained after sequencing showed 99% similarity with Enterobacter Cloacae, a gram negative rod shaped bacteria belonging to the community of PGPR. This makes it a promising strain to be developed as a biofertilizer. Additionally, biofertilizers were developed using four bacterial isolates namely, Bacillus cereus, Bacillus amyloliquefaciens, Bacilus licheniformis and Pseudomonas aeruginosa This consortium was then inoculated onto OPEFB compost and compared with uninoculated compost as control. Over a 30 day period, various types of compost analysis were also conducted. On day 30, the moisture content of inoculated compost was 83.58%. The pH was slightly acidic at 6.42 with bacterial count higher than uninoculated compost. The Germination Index (GI) was at 95% indicating that the compost was mature and free from phytotoxins. After curing, pot trials evaluating the effects of this formulation on the growth factors of Capsicum annum L, showed a significant increase in root and shoot length. Hence, combination of these bacterial strains could be a good biofertilizer for sustainable agriculture.